Searching transition year/senior cycle framework curriculum - Walsh, Orla (Veritas, 2005)
This textbook aims to explore the experience of suffering, pain and death. If we share in someone elses journey it can often helps us to understand our own journey. Searching begins by inviting students to work with three different life journeys.